Switching-based transmit antenna / aperture selection for MISO hybrid FSO / RF system - Tan, Jerome Kwee Ann (2018)
Hybrid FSO/RF systems are emerging as a cost-e ective and reliable means of constructing a back-haul network for a future wireless cellular communication. They operate on a "meet-in-the-middle" principle, combining the advantages RF back-haul systems (low cost, large operating range and non-line of sight connection) and FSO back-haul systems (high-data rate, low latency and no spectrum licence). While at the same time covering their mutually exclusive shortcomings. The use of a single-input-single-output hybrid FSO/RF system itself provides access to a high bandwidth available in the FSO link yet have improved performance over FSO links in terms of outage probability and symbol error rate (SER). Additional antennas/apertures can be added to further improve the performance of a system in a multiple-input-single-output (MISO) con guration. Transmit diversity can be achieved using a switching-based transmit antenna/aperture selection which selects the final FSO or RF link that will be used to transmit a message. In this thesis, we will explain the rationale of using a switching-based transmit antenna / aperture selection (TAS) MISO hybrid FSO/RF system. We derive the mathematical expressions for outage probability and average SER of the hybrid FSO/RF system in two di erent scenarios: 1. single link (SISO) and 2. generalized N-links (MISO). They will be conducted in three di erent systems which are as follows: 1. RF system. 2. FSO system and 3. hybrid FSO/RF system. We also present the Monte-Carlo simulation results to validate the derived analytical outage probability and average SER expressions in all six con gurations. The results show that a hybrid system with FSO/RF links improve both the outage and average SER performance of a hybrid system compared to the performance of an FSO system with an equivalent number of FSO links even when using a low-quality RF link. We also present asymptotic mathematical expression for generalized MISO FSO system to analyze the performance of a MISO hybrid system with an MISO FSO system for high symbol energy to noise ratio (SNR) values. From the simulation results, we can verify that our asymptotic expressions hold true. Lastly, we present the simulations of average SER for a Hybrid system when the RF links are subject to outdated channel state information (CSI). From the simulation results, we can infer that the average SER performance of a hybrid system is severely impacted when a TAS scheme is unable to select the optimal RF link.